EFFECT OF PEPTIDE INTERVENTION BASED ON THE CARBOXYL-TERMINAL 375STANT379 PHOSPHORYLATION SITE OF μ OPIOID RECEPTOR ON THE MORPHINE-MEDIATED RECEPTOR DOWNSTREAM SIGNALING PATHWAY - LI Xiaoyan, ZHOU Xiaohui, DONG He, DONG Mingxin (精准医学杂志, 2023)
Objective To study the effect of peptide TAT-Q368-T379 intervention based on the carboxyl-terminal 375STANT379 phosphorylation site of μ opioid receptor (MOR) on the MOR downstream signaling pathway. Methods HEK-293 cells co-transfected with HA-MOR plasmids and pGloSensorTM-22F plasmids were divided into blank group (group A), DAMGO group (group B), morphine group (group C), 0.5×10-5 mol/L peptide TAT-Q368-T379 combined with morphine group (group D), 10-5 mol/L peptide TAT-Q368-T379 combined with morphine group (group E), and 2×10-5 mol/L peptide TAT-Q368-T379 combined with morphine group (group F). The GloSensor cAMP biosensor was used to measure cAMP content in each group. HEK-293 cells co-transfection with plasmids labeled with Nanoluc at the MOR-C terminal and plasmids labeled with EYFP at the β-arrestin2-N terminal were divided into blank group (group G), DAMGO group (group H), morphine group (group I), 10-5 mol/L peptide TAT-Q368-T379 combined with morphine group (group J), and 3×10-5 mol/L Cmpd101 combined with morphine group (group K). Protein interaction analysis assay was used to determine the recruitment of β-arrestin2 after MOR activation in each group. HEK-293 cells transfected with HA-MOR plasmids were divided into blank group (group L), morphine group (group M), 10-5 mol/L peptide TA-Q368-T379 combined with morphine group (group N), and 3×10-5 mol/L Cmpd101 combined with morphine group (group O). Live cell immunofluorescence staining assay was used to determine the mean fluorescence intensity of receptors in each group. Results The results of GloSensor cAMP biosensor showed that the median effective concentration (EC50) values of groups C to F were significantly different (F=13.12,P<0.05), and the EC50 values in groups D, E, and F were significantly decreased compared with group C (P<0.05). The results of protein interaction analysis assay showed that the Emax values of groups I to K were significantly different (F=185.95,P<0.05), and the Emax values of groups J and K were significantly decreased compared with group I (P<0.01). The results of live cell immunofluorescence staining assay showed that the fluorescence intensity of cell surface receptors in groups L to O was significantly different (F=17.46,P<0.05), and the fluorescence intensity of cell surface receptors in groups N and O was significantly increased compared with group M (P<0.01). Conclusion The peptide TAT-Q368-T379 designed based on the carboxyl-terminal 375STANT379 phosphorylation site of MOR can effectively enhance the activation of morphine-mediated MOR downstream G protein signaling pathway, reduce morphine-mediated β-arrestin2 recruitment, and thus reduce morphine-mediated MOR endocytosis.